2011
DOI: 10.1007/s11103-011-9776-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the GH3 family of acyl adenylases in rosids

Abstract: GH3 amino acid conjugases have been identified in many plant and bacterial species. The evolution of GH3 genes in plant species is explored using the sequenced rosids Arabidopsis, papaya, poplar, and grape. Analysis of the sequenced non-rosid eudicots monkey flower and columbine, the monocots maize and rice, as well as spikemoss and moss is included to provide further insight into the origin of GH3 clades. Comparison of co-linear genes in regions surrounding GH3 genes between species helps reconstruct the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 80 publications
(140 reference statements)
4
74
0
Order By: Relevance
“…These data indicate that these genes are under a range of transcriptional controls. Similarly, variations in patterns of transcription have been observed in other species (Gee et al, 1991;Terol et al, 2006;Fu et al, 2011a;Okrent and Wildermuth, 2011;Kumar et al, 2012). If we conclude from the above evidence that there is a degree of specialization among the six grapevine IAA-conjugating enzymes, why are there likely to be only two JA-conjugating enzymes and one enzyme with unknown function?…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These data indicate that these genes are under a range of transcriptional controls. Similarly, variations in patterns of transcription have been observed in other species (Gee et al, 1991;Terol et al, 2006;Fu et al, 2011a;Okrent and Wildermuth, 2011;Kumar et al, 2012). If we conclude from the above evidence that there is a degree of specialization among the six grapevine IAA-conjugating enzymes, why are there likely to be only two JA-conjugating enzymes and one enzyme with unknown function?…”
Section: Discussionmentioning
confidence: 54%
“…A study of the evolutionary history of the GH3 family in rosids has indicated that grapevine is a basal rosid whose ancestor had nine GH3 genes (Okrent and Wildermuth, 2011). It was suggested that one of these genes has been lost during evolution to leave grapevine with the eight genes that the authors identified from the genomic sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This diverse group of enzymes catalyzes the addition of AMP to carboxyl groups on a wide variety of substrates and typically contains three conserved motifs that form a binding pocket for ATP and AMP substrate intermediates (11). GH3 proteins regulate the activity of plant hormones through amino acid conjugation and have a substantial effect on plant metabolism and physiology (12). For example, FIN219 catalyzes the conjugation of isoleucine (Ile) to JA, forming jasmonoyl-isoleucine (JA-Ile).…”
mentioning
confidence: 99%
“…In the second transfer step, the amine group of an amino acid nucleophilically displaces AMP, yielding the conjugated acyl acid [10]. GH3 proteins regulate the levels of phytohormones, including JA and IAA [11]. Group I GH3 genes catalyze additional amino acids to phytohormone JA-Ile and Group II GH3 genes catalyze additional amino acids to phytohormone IAA.…”
Section: Introductionmentioning
confidence: 99%